(3OhQ GdbVGA GdOhdj aj MeGjI Mbhb GdEfSGf (B/s - (3GdYjSGhj, egfO LGSe eMeOs ((3GdLjRI, eUQ (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2022)
(3Ef EbGeI LgGJ bVGFjI YGOdI heSJbdI TQW dGRe dEQSGA GdYOGdI aj Cj eLJeY ; adG bjeI ddbGfhf eG de Jbe Ydi JWHjbg LgI bVGFjI YGOdI eSJbdI, hGdeLJeY GdOhdj TCfg aj Pdc TCf HbjI GdeLJeYGJ, aZjGH LgI bVGFjI JVef GMJQGe hJWHjb bhGYO GdbGfhf GdOhdj jLYd Pdc GdbGfhf YOje GdLOhi hYQVI ddGfJgGc, haj Xd GdCMOGK GdJGQjNjI GdJj TgOgG GdeLJeY GdOhdj GdJj COJ Edi TMP GdacQ hGdYbd hGdefWb hMK GdNWi aj SHjd hVY bhGYO LOjOI hLOjI JhGcH Mbhb GdEfSGf hMbg aj GdMjGI GdJj dG jYjTgG EdG eQI hGMOI ; dPdc HGJ jfXQ Edi GdbVGA GdOhdj HCfg jgOa Edi HfGA UQM jMJej Hg GdSdGe hMUf JJOQY Hg GdYOGdI ; dJfbP GdEfSGfjI faSgG ef hjdGJ GdMQhH hGdGfJgGcGJ, hbO Mbb YUQ GdeMGce GdOhdjI GdQGgf JbOeG edMhXG, hGbJQf JhSY GdhdGjI GdbVGFjI GdOhdjI HJRGjO cHjQ aj MGdGJ GdJbGVj, aJWhQ GdGNJUGU GdTNUj deMGce GdbVGA GdOhdj Ydi GdeSJhjjf GdYGdej hGdEbdjej djTed Pdc GdGNJUGU GdfXQ aj fRGYGJ jchf CMO CWQGagG CTNGUG WHjYjjf eef JfJgc Mbhbge GdebQQ MeGjJgG HehLH bhGYO bGfhfjI OhdjI, hdG jecf GdMOjK Yf OhQ ddbVGA aj MeGjI Mbhb GdEfSGf eG de Jcf YedjI GdJbGVj UMjMI hefUaI, ef MjK GSJbdGdjJgG hJeJYgG HGdNHQI GddGReI, hef MjK GdELQGAGJ GdbVGFjI hVeGf Mbhb CWQGa GdOYhi hHbjI GdCTNGU GdeGKdjf CeGe GdeMceI, hHeG Cf UMI GdJbGVj JLSO YOGdI GdbVGA, abO JVefJ GdfXe GdCSGSjI ddeMGce GdOhdjI LedI ef VeGfGJ UMI GdJbGVj, ceG aUdJ gPg GdfXe BdjGJ hTQhW GNJjGQ GdbVGI, dVeGf GSJbGeI GdeMceI hJhGRfgG, ceG Cf ddELQGAGJ OhQ gGe aj JMbjb GdYOGdI h JaYjd OhQ GdbVGA aj MeGjI Mbhb GdEfSGf, ajJe NdGdgG GdeMGaXI Ydi Mbhb CWQGa GdfRGY, hMeGjI GdCTNGU GdeCKdjf CeGe GdeMceI ef VMGjG hTghO h eTJHg Hge heJgejf(B.s
(3bGFeI eNJUQGJ (B: (3UaMI (B547-548.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B501-546.s
Keywords: (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s; (3GdMbhb GdeOfjI (B((3bGfhf Ohdj(B)s